1978
DOI: 10.1111/j.1570-7458.1978.tb02806.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inhibitory Stimuli in the Choice of Oviposition Site by Phytophagous Insects

Abstract: The examination of substrate selection for oviposition behaviour by specialist phytophagous insects like Acanthoscelides obtectus, Bruchus pisorum, and Pieris brassicae, revealed that such processes were governed by information probably obtained through similar receptors to those taking part in feeding preference or rejection. The role of the ovipositor is assumed to be secondary or negligible. The receptors respond to a wide variety of inorganic or organic compounds of very dissimilar structure which inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…These have revealed that the palatability of a chemical or plant is relative to the available alternatives (Meisner and Ascher, 1972;Jermy and Szentesi, 1978;Richardson and Whitaker, 1982), and to the gustatory background against which the chemicals are presented. Measures of palatability based on choice tests between two concentrations may differ from ones based on tests between each concentration and a control.…”
Section: No-choice and Choice Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…These have revealed that the palatability of a chemical or plant is relative to the available alternatives (Meisner and Ascher, 1972;Jermy and Szentesi, 1978;Richardson and Whitaker, 1982), and to the gustatory background against which the chemicals are presented. Measures of palatability based on choice tests between two concentrations may differ from ones based on tests between each concentration and a control.…”
Section: No-choice and Choice Testsmentioning
confidence: 97%
“…In testing contact chemoreception and oviposition by Acanthoscelides obtectus, Jermy and Szentesi (1978) used glass slides and glass beads coated with test chemical in 2% starch solution. Woodhead and Bernays (1977) avoided substrates by presenting chemicals directly to the mouthparts with a syringe.…”
Section: Artificial Substratesmentioning
confidence: 99%
“…In many phytophagous insects the host plant spectrum is decisively determined by the botanical distribution of chemicals acting as feeding or oviposition deterrents (Dethier, 1980a;Jermy, 1966;Jermy and Szentesi, 1978;Schoonhoven and Jermy, 1977). Contact chemoreceptors sensitive to a wide variety of compounds have been identified in all species of Lepidoptera where such cells have been looked for (Schoonhoven, 1972a).…”
Section: Deterrents From Non-host Plantsmentioning
confidence: 98%
“…Although the majority of insects can depend on plant chemistry to guide their selection of the most suitable site for development and survival of their progeny, plant chemistry may lead to 'mistakes' (Jermy & Szentesi 1978;Rodman & Chew 1980;Renwick 1989). Reported 'mistakes' by females laying eggs on plants that do not support larval development have been traced to chemical similarity of the plants to actual hosts (Chew 1977a;Rodman & Chew 1980;Renwick 1989;Jaenike 1990).…”
Section: Resultsmentioning
confidence: 97%